Analysis of Lethal Outcomes in the Cases of Sefere Acute Pneumonia Associated with Influenza A (H1N1) Pdm09 - Sergeeva IV (Journal of Global Pharma Technology, 2017)
The article analyzes 9 pathology records of deaths from severe complicated influenza A (H1N1) pdm09.It was found that among the deceased were predominantly young women aged 25 to 40 years with a burdened premorbid background, 77.8% of cases. Risk factors were: metabolic syndrome in 77.8% of cases and cardiovascular diseases, chronic viral hepatitis, chronic pyelonephritis was diagnosed in 11.1% of cases, respectively. Lethal outcome follows as a result of ARF and acute respiratory distress syndrome. Severe total injury of the trachea, lungs, and bronchi associated with internal organs plethora was detected morphologically. Clinical manifestations of ARF and ARDS were combined morphologically with alveolar damage. In all cases of lethal outcome, diffuse alveolar damage and polyorganism changes were diagnosed.Keywords: Influenza A (H1N1) pdm09, Community-acquired pneumonia, Lethal outcome.